Interconnected marine habitats form a single continental-scale reef system in South America - Carneiro, Pedro B. M. (2022)
Large gaps in reef distribution may hinder the dispersal of marine organisms, interrupting processes vital to the maintenance of biodiversity. Here we show the presence and location of extensive reef habitats on the continental shelf between the Amazon Reef System (ARS) and the Eastern Brazilian Reef System (ERS), two reef complexes off eastern South America. Formations located 20–50 m deep include both biogenic and geogenic structures. The presence of diverse reef assemblages suggests the widespread occurrence of rocky substrates below 50 m. These habitats represent an expansion of both the ARS and ERS and the closure of the only remaining large-scale gap (~ 1000 km) among West Atlantic reef environments. This indicates that the SW Atlantic harbors a single, yet heterogeneous, reef system that stretches for about 4000 km, and thus, represents one of the largest semi-continuous tropical marine ecosystems in the world.